INTENSIVE METHODS OF PRACTICAL FOREIGN LANGUAGE LEARNING (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The problem of psychological self-regulation has always been considered relevant. Psychological (mental) self-regulation is self-regulation using mental and modeling means of reflecting truth and discontent. There is also the concept of mental self-regulation, the concept of linking the real state of a person with self-regulation. In the process of self-regulation, a person can get three effects: calming (elimination of emotional tension), restorative (outflow of fatigue) and activating effect. At the same time, the main purpose of mental self-regulation is the implementation and management of current activities.